7. ASSESSMENT OF NUTRITIONAL STATUS OF PATIENTS WITH COPD AT THONG NHAT DONG NAI GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Currently, Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of death, malnutrition accounts for a quite high rate in COPD patients and affects the effectiveness of treatment, reducing quality of life of patients, increasing hospital stay, increasing treatment costs, therefore assessment of malnutrition in COPD patients is very necessary. Research objective: the study is to evaluate the nutritional status of chronic obstructive pulmonary disease patients at Thong Nhat hospital - Dong Nai in 2023. Research method: Cross-sectional descriptive study conducted on 111 patients Kernels were collected by convenience sampling. Results: The proportion of malnourished patients with BMI < 18.5 was 60.4%; 45.9% of patients with borderline MAC had SDD; 64% of patients were at risk of malnutrition according to SGA; There was a relationship between the rate of malnutrition according to BMI compared to age group and the highest rate was in the group ≥ 60 years old, there was a difference between the sexes with a higher rate in women. Conclusion: The rate of malnutrition in COPD patients is quite high, so there needs to be measures to improve the nutritional status of COPD patients at the hospital.
Keywords: Malnutrition, chronic obstructive pulmonary disease.